Prototipo selector de café empleando el sensor CNY70 para identificar frutos verdes (2021)
This article presents the development of a coffee selector prototype using the CNY70 sensor that is used to identify green fruits and separate them from ripe ones. The focus of this work is descriptive and as a result the automation of the selection process of the green coffee fruit was obtained, allowing to obtain a product with more homogeneous characteristics in terms of the maturity of the fruits, directly improving its quality.